Allostatic load and canine companionship: a comparative study using biomarkers in older adults - Alejandro Morales-Jinez; Francisco J. López-Rincón; Alicia Ugarte-Esquivel; Irma Andrade-Valles; Luz Elena Rodríguez-Mejía; José Luis Hernández-Torres (Universidade de São Paulo, 2018)
ABSTRACT Objective: to compare the biomarkers and the allostatic load levels in a sample of older persons with and without canine companionship. Method: descriptive and comparative study. Data were collected using a sociodemographic questionnaire and a fasting blood sample. The allostatic load comprised 11 biomarkers that are primary and secondary stress mediators, which arise from the following systems: neuroendocrine, immune, metabolic, cardiovascular and anthropometric. Results: a significant difference was found in two biomarkers: cortisol (t= -3.091, df=104, p=0.003) and total cholesterol (t= -2.566, df=104, p=0.012), in the allostatic load levels between older adults with and without a canine companionship (U= 1714.00, Z= 2.01, p=0.044). By associating the allostatic load level with the canine companionship, there was a higher frequency of older adults with low allostatic load among those who have canine companion, compared with those who do not have canine companionship. (χ2= 3.69, df=1, p= 0.043). Conclusion: canine companionship influences health in a positive way, as the allostatic load is lower in older adults who have a dog as companion, in addition to presenting lower levels of cortisol and total cholesterol.